PENGENDALIAN BUMDESA DALAM MENINGKATKAN PENDAPATAN ASLI DESA - Lutfiyah, Idza; Sutikno, Chamid; Satwika Wijaya, Shadu (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2024)
This study aims to describe how the process of controlling BUM Desa Ujub Srowot in Srowot Village, Kalibagor District, Banyumas Regency in increasing PADes in terms of control environment, risk assessment, control activities, information & communication, and monitoring aspects. This study uses a qualitative descriptive research method. Data collection techniques used by researchers are interviews, observation, and documentation. The data sources used are primary data and secondary data. The results showed that the control process carried out by BUM Desa Ujub Srowot in an effort to increase the village’s original income is in accordance with existing control aspects starting from the control environment with a structure formed according to the SOP, risk assessment with reguler report, control acivities wuth meetings and deliberations related to the use of technology, information and communication are held by all parties, monitoring (supervision) is carried out by the outhorized parties therein. However, over all aspects of control are not yet maximal, one of which is related to supervision.